Exploring identity in coaching – insights into coaches’ understanding and approach - Lazarus, Alex (Frontiers in Psychology, 2025)
This research project is in response to a recent increase in identity theorising across academia, in business and in politics as a reaction to times of the tumultuous socioeconomic climate found to have direct ramifications on people’s identities. In consideration of the fact that striving to attain a positive identity is fundamental to all human beings, given the role of coaches as societal agents and through identifying that the concept of identity is becoming one of the key themes in HRD, this paper placed attention to identity from a perspective of individual coaches and on behalf of the coaching industry. Subsequently, the aim of this paper was to contribute new insights about the theme of identity in coaching based on findings drawn from empirical research specifically about coaches’ knowledge, awareness and understanding of identity in the process of coaching. The paper also set out to explore coaches’ choice of methodology and tools when coaching on issues of identity and it posed questions related to coach education in relation to the theme of identity. In the absence of theory and past research on identity coaching recognised in the literature review, this qualitative experiential research project was conducted through semi-structured interviews with fourteen experienced executive coaches. This study has highlighted that the nature of executive coaching had the capacity to move towards a whole-person approach enriched by an increasing more explicit introduction of themes brought to coaching which reside at deeper psychological levels and are concerned with people’s identities. Based on the findings, the research put forward recommendations with regards to rethinking what executive coaching is, introducing a more systematic approach of identity coaching, improvement to coach education and future research to create a body of knowledge that will enable the coaching practitioners to be effective at coaching at the level of coachees’ identity.